Densification and Microstructural Evolution of Hierarchically Porous Ceramics During Sintering. Issue 11 (23rd September 2015) - Shang, Haixia; Mohanram, Aravind; Bordia, Rajendra K.
Abstract : Several technologically important ceramics are porous. One common approach to make high porosity ceramics is to use fugitive pore formers followed by partial densification. The resultant ceramic has hierarchical porosity: extrinsic large pores from the burnout of the pore former; and intrinsic small inter‐particle pores. In this study, the effect of sintering conditions and pore former on porosity and microstructure of hierarchically porous ceramics has been investigated. Pore size and pore volume fraction evolution of intrinsic and extrinsic pores were quantified as a function of sintering conditions. The effect of porosity and sintering conditions on average grain size is also investigated. It is shown that during sintering both the extrinsic and the intrinsic porosity decrease but along different trajectories. It is shown that the intrinsic pores control the grain growth. The results are discussed in terms of standard mechanisms and models available in the literature.